MENINGKATKAN MINAT BELAJAR BIOLOGI MENGGUNAKAN PEMBELAJARAN CTL (Contextual Teaching and Learning) PADA SISWA DI KELAS VII-B MTs NEGERI PURWOKERTO - Teguh Julianto (Khazanah Pendidikan, 2010)
Improving Student’s Interest in Biology lesson by using contextual teaching and learning (CLT) methods is n action research study which had an aim to improve student’s interest in biology. The indicator of student’s interest covers the student’s diligence in learning process, active in following teaching and learning process, active in doing a task, the facility and the sources of learning. The result of this researched showed that there were an improvement of students learning interest. The percentage result in cycle I was 39.5%, in cycle 2 was 72.67% and in Cycle 3 was 80.92%. The improvement of students learning interests gave a positive effect toward the students achievement. The students learning achievement in cycle 1 I was 39%, in cycle II was 82% and in cycle III was 93%. In conclusion Contextual Teaching and Learning (CLT) can improve the students learning interest in Biology at the Second Grade Students of MTs Negeri Purwokerto. Key words : Improving, Student’s learning interest, Contextual Teaching and Learning (CTL)